Macroeconomic Analysis of the Greece's Sovereign Debt and Identification of Key Assets - Balomenos, Evžen (2023)
This master thesis presents a macroeconomic examination of the contemporary Greek economy and its assets. Employing quantitative research methods, this study evaluates the impact of the sovereign debt crisis on the Greek economy and assesses the sustainability of the current debt levels. The research also delves into trends and prospects within Greece's asset market, predominantly focusing on investment opportunities that can potentially cover the fiscal deficit in Greece. The findings of this analysis yield valuable insights into the current landscape of the Greek economy and its future trajectory. The study concludes with a set of policy recommendations aimed at fostering the future growth of the Greek economy and proposes a list of key industry stimulants.